Gap Analysis of Service Quality in Hotel Industry - Singla, vikas; Singh, Amar Jnder (Gyan Management Journal, 2009)
The purpose u/this study was lo asses.i Lite perceptions of service quality in hotel industry ji-om the perspective of both tourists a11d hotel ma11ager . Such a11 approach makes possible the ide11tificalion and analysis ofperccj1lual gaps between the two particJ. Cive,i the iypically high level of personal interaction in professional service encounlers, the examin(/tion of bot It /Jar ties parlicij>aling i11 the exchange is necessary far gaining 1mdersta11di11g of the evaluation process. The study identified a number of gaps ex isling between the perceptions of customers a11rl those of providers. The study further suggested that 011e of the princ1jJal causes of the gaps between the perceplio11s of the. customers aud providers was i/ze assumption amongst providers that Ikey know and understand customers' expeclatio11s, whereas tltey !tad the Least contact w1lh rnstomers and were not able to t1ssess customer needs accurately.
Keywords: llotcl Inulustry; Gap Model; Sernice Qyality